2011
DOI: 10.1063/1.3632050
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous electrolytes confined within functionalized silica nanopores

Abstract: Molecular dynamics simulations have been carried out to investigate structural and dynamical characteristics of NaCl aqueous solutions confined within silica nanopores in contact with a "bulk-like" reservoir. Two types of pores, with diameters intermediate between 20 Å and 37.5 Å, were investigated: The first one corresponded to hydrophobic cavities, in which the prevailing wall-solution interactions were of the Lennard-Jones type. In addition, we also examined the behavior of solutions trapped within hydrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
49
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 54 publications
6
49
1
Order By: Relevance
“…The structure of water and aqueous solutions in hydrophilic confinements of interest in energy applications has been a popular subject for molecular dynamics simulations for a long time. While we cannot give an exhaustive review, some relevant examples include the work of Leung and others on salt water in model silica pores 3,4 , as well as the studies of Argyris et al 5 and Videla et al 6 . Ho et al considered the effect of varying silica protonation states on the structure of the confined aqueous solution 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The structure of water and aqueous solutions in hydrophilic confinements of interest in energy applications has been a popular subject for molecular dynamics simulations for a long time. While we cannot give an exhaustive review, some relevant examples include the work of Leung and others on salt water in model silica pores 3,4 , as well as the studies of Argyris et al 5 and Videla et al 6 . Ho et al considered the effect of varying silica protonation states on the structure of the confined aqueous solution 7 .…”
Section: Introductionmentioning
confidence: 99%
“…16 Consequently, in recent years molecular simulations have been employed to investigate structural, dynamics, and dielectric properties of water confined in silica nanopores of various sizes, geometries, and hydrophilic/hydrophobic features. 2,3,[16][17][18][19][20][21][22][23][24] However, most of these studies only reported results for aqueous solutions confined inside uncharged systems. In contrast, only few works have focused on the properties of aqueous solutions confined into charged silica nanopores.…”
Section: Introductionmentioning
confidence: 99%
“…Water-explicit simulations of charged surfaces in principle include all these effects and should thus allow for a crucial test of the assumption of additive hydration and PB pressures, in particular since the surface charge and its location are precisely known. Previous simulations reported ion density profiles between nanometer-separated charged surfaces [10][11][12][13]25 .…”
mentioning
confidence: 99%